A study on the factors influencing the preference of Sri Lankan consumers for the use of denim jeans - KARUNARATNE P.V.M; WIJAYAKURUPPU M. B. M. W; WIJAYAPALA U. G. S; RANATHUNGA G. M (Journal of Advanced Research in Social Sciences and Humanities, 2020)
Aim: This paper analyzes the current demand for denim apparel in Sri Lanka to determine the factors influencing consumer preferences when purchasing denim jeans. Women’s denim jeans are trending due to a wide variety of flattering cuts and washes. According to the data, women were more likely to buy denim jeans, and they were increasingly interested in the fashion industry. Although research has been done to assess consumer preference in the Sri Lankan denim fashion apparel market, it has yet to be useful in determining how consumers feel about denim jeans globally.Method: The researchers used a questionnaire to evaluate factors of preference for buying denim jeans. We received 88 completed surveys from interested consumers.Findings: When shopping for denim jeans, 85.5% of consumers place a high priority on quality, according to the data. This research lends credence to the idea that consumers’ tastes in denim jeans are complex and multifaceted. Results were analyzed, and it was determined that some of the suggestions could be implemented in future product development to improve the quality and aesthetic appeal of denim jeans sold in the Sri Lankan denim apparel fashion market.Implications/Novel Contribution: Although denim jeans are a staple in Sri Lankan wardrobes, there is a paucity of research into consumer consumers for this ubiquitous product. To improve the future of retail fashion in Sri Lanka, this study reveals some crucial facts about denim apparel brands and factors of preference of such consumers.